2012
DOI: 10.1371/journal.pone.0039513
|View full text |Cite
|
Sign up to set email alerts
|

Medical Care and Payment for Diabetes in China: Enormous Threat and Great Opportunity

Abstract: BackgroundThe Diabetes Impact Study followed up a large national population-based screening study to estimate the use of and expenditures for medical care caused by diabetes in China and to ascertain the use and cost of essential basic medicines and care.MethodsIn 2009–10, the study team interviewed 1482 adults with diabetes and 1553 adults with glucose tolerance in the normal range from population-based random samples at 12 sites in China. The response rate was 67%.FindingsAfter adjusting for age, sex, and ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 32 publications
1
59
3
Order By: Relevance
“…In the Hong Kong Diabetes Registry, \15 % of the patients were using lipid lowering drugs at baseline [30]. In contrast, a large survey in China showed that only 1.9 % of Chinese with diabetes in the urban areas used lipid lowering drugs, including that 1.7 % used statins [31]. The users of lipid lowering drugs without CVD and hyperlipidemia in this study might only account for a small proportion of the total sample.…”
Section: Discussionmentioning
confidence: 59%
“…In the Hong Kong Diabetes Registry, \15 % of the patients were using lipid lowering drugs at baseline [30]. In contrast, a large survey in China showed that only 1.9 % of Chinese with diabetes in the urban areas used lipid lowering drugs, including that 1.7 % used statins [31]. The users of lipid lowering drugs without CVD and hyperlipidemia in this study might only account for a small proportion of the total sample.…”
Section: Discussionmentioning
confidence: 59%
“…It has been estimated that a total of 12.9 million people died from ischemic heart disease and stroke in the world, while diabetes is the main risk factor [5, 6]. Studies have shown that good glycemic control is critical for patients with type 2 diabetes mellitus (T2DM), since the HbA1c level is correlated with diabetic complications [7, 8]. However, according to the latest survey among 22.31 million Chinese T2DM patients, it was shocking that more than two-thirds could not effectively control their HbA1c levels [9].…”
Section: Introductionmentioning
confidence: 99%
“…The medical and economic burden of diabetes is an important public health challenge for China. However, at present, there is no systematic prevention strategy for diabetes, despite the fact that it is considered a fundamental component of the nation’s health policies [9]. …”
Section: Introductionmentioning
confidence: 99%